Roles of Zinc Signaling in the Immune System - Shintaro Hojyo; Toshiyuki Fukada (Journal of Immunology Research)
Zinc (Zn) is an essential micronutrient for basic cell activities such as cell growth, differentiation, and survival. Zn deficiency depresses both innate and adaptive immune responses. However, the precise physiological mechanisms of the Zn-mediated regulation of the immune system have been largely unclear. Zn homeostasis is tightly controlled by the coordinated activity of Zn transporters and metallothioneins, which regulate the transport, distribution, and storage of Zn. There is growing evidence that Zn behaves like a signaling molecule, facilitating the transduction of a variety of signaling cascades in response to extracellular stimuli. In this review, we highlight the emerging functional roles of Zn and Zn transporters in immunity, focusing on how crosstalk between Zn and immune-related signaling guides the normal development and function of immune cells.